(untitled) (Journal of Environmental Science and Natural Resources, 2015)
A cross sectional study was conducted to find out the prevalence and underlying causes of childhood overweight and obesity among 7 selected English medium schools of Dhaka, Bangladesh. For study purpose, 112 participants were selected from English medium schools located different places of Dhaka city to collect data through a well structured questionnaire by face to face interview. The prevalence of overweight and obesity was found 20.5% and 24.1 % respectively and also the prevalence of overweight and obesity among boys were 16.4% and 26.9% respectively, and for girls were 26.7%, 20.0% respectively. Most (7.46% and 8.95%) of the male obese students were in the age group of 9-10, 13-14 years and most (6.67% and 6.67%) of the female obese students were in the age group of 9-10 & 11-12 years. The prevalence of overweight and obesity was found quite high in this study. It is demonstrated that several risk factors such as more meal taking habit, snacking habits, physically less active lifestyle and high levels of sedentary activities to be major underlying factors for increasing prevalence of childhood overweight and obesity among English medium school children in Dhaka, Bangladesh. DOI: http://dx.doi.org/10.3329/jesnr.v7i1.22146 J. Environ. Sci. & Natural Resources, 7(1): 63-67 2014